The Cytoskeletal Network Controls c-Jun Expression and Glucocorticoid Receptor Transcriptional Activity in an Antagonistic and Cell-Type-Specific Manner - Oren, Anat (American Society for Microbiology, 1999)
The physical and functional link between adhesion molecules and the cytoskeletal network suggests that the cytoskeleton might mediate the transduction of cell-to-cell contact signals, which often regulate growth and differentiation in an antagonistic manner. Depolymerization of the cytoskeleton in confluent cell cultures is reportedly sufficient to initiate DNA synthesis. Here we show that depolymerization of the cytoskeleton is also sufficient to repress differentiation-specific gene expression. Glutamine synthetase is a glia-specific differentiation marker gene whose expression in the retinal tissue is regulated by glucocorticoids and is ultimately dependent on glia-neuron cell contacts. Depolymerization of the actin or microtubule network in cells of the intact retina mimics the effects of cell separation, repressing glutamine synthetase induction by a mechanism that involves induction of c-Jun and inhibition of glucocorticoid receptor transcriptional activity. Depolymerization of the cytoskeleton activates JNK and p38 mitogen-activated protein kinase and induces c-Jun expression by a signaling pathway that depends on tyrosine kinase activity. Induction of c-Jun expression is restricted to Müller glial cells, the only cells in the tissue that express glutamine synthetase and maintain the ability to proliferate upon cell separation. Our results suggest that the cytoskeletal network might play a part in the transduction of cell contact signals to the nucleus.